The submerged genitive in Old Prussian - Petit, Daniel (Vilnius University Open Series, 2021)
This paper is devoted to the Old Prussian phrase ʃwaiāʃmu ʃupʃei buttan ‘to his own house’ (Enchiridion, III 876). Far from being simply the result of a syntactic error, the genitive ʃupʃei ‘of oneself’ can be recognized as the reflex of an archaic syntactic pattern, the “submerged genitive”, which has left numerous traces in Baltic and other Indo-European languages (Slavic, Greek, Latin, Old High German).
Keywords: syntax; possessive; genitive; agreement